Optimization of thermal characteristics of buried composite phase-change energy storage walls based on nonlinear engineering methods - Diao Rongdan; Feng Hao; Chi Congwen; Michel Mushagalusa Murhambo; Guan Yajuan; Guerrero Josep M. (Nonlinear Engineering)
Nonlinear engineering methods improve the thermal insulation of building walls and save energy. This study proposes multiple construction forms of embedded composite phase-change energy storage walls to study heat transfer and its impact on indoor environments based on nonlinear engineering methods. The study reveals heat transfer laws and mechanisms affecting indoor environments. The results show a <10% error between measurements and numerical simulations, validating numerical methods for studying phase-change walls. Without water flow, temperature differences at the base of ordinary, S-font, U-font, and back-font phase change walls are 8.70, 8.80, 8.83, and 8.94°C, respectively. With water flow, these differences are 5.00, 5.18, and 6.51°C. Smaller coil spacing enhances heat storage. Phase-change walls reduce indoor air temperature by up to 3.2°C, improving thermal comfort. By combining nonlinear engineering methods, technical support is provided for achieving green buildings and sustainable development.